Locus of control moderates the relationship between headache pain and depression - Heath, Robin L. (Springer Milan, 2008)
The aim of the current study was to triangulate qualitative and quantitative data in order to examine in greater detail the relationship between self-reported headache pain severity, depression and coping styles. Psychosocial scales, headache characteristic scales and in-depth interviews were administered to 71 adults with the diagnosis of primary headache. Regression analyses with the scales showed that greater self-reported headache pain severity was associated with higher levels of depression. A high internal locus of control weakened the relationship between the headache severity and depression variables. The qualitative data supported the relationship between pain severity and internal locus of control and, in addition, revealed that perceived efficacy of pharmacologic intervention might be a related factor. The results suggested that stronger coping skills might reduce depression among headache sufferers.